Validation of the Thai version of the Female Genital Self-Image Scale (FGSIS) - Wanchat Komon; Athasit Kijmanawat; Kitti Chattrakulchai; Sirirat Sarit-apirak; Chatchawan Silpakit; Jittima Manonai (BMC, 2022)
Abstract Background Female genital self-image is associated with sexual health, sexual behavior, and gynecologic health behavior. The Female Genital Self-Image Scale (FGSIS) is a simple, validated instrument that quantifies genital self-image in women. The study aim was to translate the original English FGSIS into Thai and test its psychometric properties among Thai-speaking women. Methods A cross-sectional, psychometric study of sexually active women attending a health check-up clinic at a university hospital in Thailand was conducted. On a volunteer basis and convenience sampling, 90 sexually active women were recruited between December 2020 and January 2021. Translation and transcultural adaptation of the English FGSIS into Thai were performed. The validity and reliability of the Thai FGSIS were assessed by examining content validity, face validity, internal consistency, construct validity, and test-retest reliability. The content validity of the Thai FGSIS was evaluated by assessing missing values, and internal consistency was evaluated using Cronbach's alpha. Scores on the FGSIS and the Female Sexual Function Index (FSFI) were compared to examine convergent validity (using Pearson correlations). Confirmatory factor analysis (CFA) was also conducted. Test-retest reliability was measured by re-administering the Thai FGSIS to the same group of respondents after a 2-week interval. Results The final Thai FGSIS was developed and assessed by a panel of experts. Data were examined for 86 respondents with average age of 32.5 ± 9.11 years. Content validity assessed using the level of missing data demonstrated no missing items. The overall internal consistency was high (Cronbach's alpha: 0.847). Strong correlations (r = 0.61-0.83) between FSFI and FGSIS total scores (p < 0.01) were demonstrated. In addition, five domains of sexual functioning and the FSFI total score showed high correlations ranging from r = 0.089 to r = 0.383 (p < 0.05), which confirmed convergent validity. CFA identified a two-factor structure for the Thai FGSIS. The test-retest reliability for 38 participants was 0.937 (p < 0.05). Conclusion The Thai FGSIS was found to be a highly valid and reliable instrument with which to measure female genital self-image in Thai-speaking women.